1995
DOI: 10.1099/13500872-141-4-831
|View full text |Cite
|
Sign up to set email alerts
|

Inducible expression of heterologous genes targeted to a chromosomal platform in the cyanobacterium Synechococcus sp. PCC 7942

Abstract: High-level, inducible expression of heterologous genes in the cyanobacterium Synechococcus sp. strain PCC 7942 was obtained using the Escherichia coli trc promoter and lac/ repressor. The pet€ gene of Anabaena sp. strain PCC 7937 encoding plastocyanin precursor protein and the €. coli uidA gene encoding )?-glucuronidase were initially placed under the control of the trc promoter and lac/ repressor by cloning into the E. coli pTrc99C expression vector and were introduced into the chromosomal platform for integr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
46
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 30 publications
3
46
0
Order By: Relevance
“…While some essential genes striction enzymes to excise the region coding for the 43-have already been identified (22,23, and references kDa N-terminal domain and replace it by that encoding therein), it has also been shown that it is possible to the 24-kDa domain. The resulting plasmid was named express heterologous proteins in this strain (24,25), pBL24K (Fig. 1A).…”
mentioning
confidence: 99%
“…While some essential genes striction enzymes to excise the region coding for the 43-have already been identified (22,23, and references kDa N-terminal domain and replace it by that encoding therein), it has also been shown that it is possible to the 24-kDa domain. The resulting plasmid was named express heterologous proteins in this strain (24,25), pBL24K (Fig. 1A).…”
mentioning
confidence: 99%
“…The construct was recombined into a specific site of the genome, NSII, in which DNA insertion per se did not affect the fundamental cell activity or circadian rhythm. And at NSII, the inducible promoter trc used here had functioned in Synechococcus (6,9,17). To control the down-regulation of kaiA expression, we used the transcription-translation interference technique, using antisense transcription in Synechococcus (25).…”
Section: ϫ457-ϩ11mentioning
confidence: 99%
“…Molecular genetic techniques, e.g., efficient transformation and gene targeting by precise homologous recombination, have been used for studying the cyanobacterial Synechococcus sp. strain PCC 7942 (3,6,24). By integrating molecular genetic properties and a monitoring system for the in vivo gene expression of bioluminescence, we previously isolated several types of clock mutants that exhibited altered bioluminescence rhythms, including short-or long-period rhythms and even arrhythmias (16).…”
mentioning
confidence: 99%
“…strain PCC 7942 R2-PIM8 (smtA) [7] to produce an organism with enhanced toxic metal sequestration capability. Metallothioneins are low-molecular-weight, cysteine-rich proteins that chelate certain metals as mercaptide complexes [14].…”
mentioning
confidence: 99%
“…All plasmids were propagated in E. coli DH5␣. The pTrcIK cloning vector is described in [7]. The plasmid pJW6 [6] was the source for the Saccharomyces cerevisiae CUPI gene.…”
mentioning
confidence: 99%